The geomechanical properties of soils treated with nanosilica particles - Gizem Aksu; Tugba Eskisar (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
This study examines the effect of nanosilica (NS) additive to improve the mechanical properties of clay, clayey sand, and sand. The engineering properties of the soils were investigated through Atterberg limits, compaction, unconfined compression, ultrasonic pulse velocity (UPV), freeze-thaw, and direct shear tests. The NS content varied from 0% to 0.7% and cement content was 5% and 10% by the dry weight of the soil. The curing period varied from 7 d to 150 d. The consistency, compaction, and strength properties of the soils were affected by the presence of NS and cement. The optimum NS contents in clay specimens with 5% and 10% cement were 0.5% and 0.7%, respectively. It was 0.7% in sand specimens with both cement ratios, as well as 0.3% and 0.7% in clayey sand specimens with 5% and 10% cement, respectively. In terms of freeze-thaw resistance, clayey sand specimens containing 0.5% NS and 10% cement had the minimum strength loss. Exponential relationships existed between the ultrasonic pulse velocity (UPV) and the unconfined compressive strength (UCS) of soil specimens having the same curing period. The shear strength parameters of the soils also improved with the addition of NS. Scanning electron microscope (SEM) images demonstrated that cement and NS contributed to the improvement of the soils by producing a denser and more uniform structure. It was concluded that the minor addition of NS could potentially improve the geomechanical properties of the soils.